A(H1N1) 2009 Flu in the Territory of Krasnoyarsk - I. V. Sergeeva (Проблемы особо опасных инфекций, 2010)
The results of analysis of case records of patients with type A flu, caused by A(H1N1) 2009 virus are presented. The greatest susceptibility to the disease is registered among young people of 16-20 years old. Dry paroxysmal cough and intoxication are shown to be the main symptoms of A(H1N1) 2009 flu. Severe course of the disease with complications is registered in the 24-44-year-old age group. The risk group includes pregnant women and patients with metabolic syndrome.